Yet another new cosmological argument - Weaver, Christopher (International journal for philosophy of religion, 2016)
I argue that the existence of a necessary concrete being can be derived from an exceedingly weak causal principle coupled with two contingent truths one of which falls out of very popular positions in contemporary analytic metaphysics. I then show that the argument resists a great many objections commonly lodged against natural theological arguments of the cosmological variety.